Yeraltı sudan enerji istehsalı imkanlarının qiymətləndirilməsi (Nabran istirahət zonası timsalında) - Tərlanov, Firuz; Məmmədova, Vüsalə; Bayramov, Emin (My University, 2024)
The chemical composition of the groundwater in the Nabran recreational area was studied. The water from the springs is fresh, hard in terms of total hardness, and neutral in pH. The chemical composition of the groundwater from the springs is calcium bicarbonate.
Assessment of the potential for energy production from groundwater (on the example of the Nabran recreation area)
Keywords: Termal sular; Azərbaycanın termal su mənbələri; Thermal water sources of Azerbaijan; Thermal waters